ANALISIS PEMAHAMAN SISWA TENTANG PENDIDIKAN SEKS DALAM MEMBENTUK KARAKTER PEDULI KESEHATAN PADA PEMBELAJARAN BIOLOGI - hayati hayati; Ika Chastanti; Risma Delima Harahap (Universitas Negeri Medan, 2019)
One of the juvenile delinquency problems is one that is related to sexual activities such as sexual abuse and violence, premarital sex, premarital pregnancy, abortion, sexual homo, marriage at a young age, free sex, and sexually transmitted diseases, things this can affect the readiness of adolescents for they future. Therefore to shape the character of caring for students' health, especially reproductive health, the main solution is to introduce and teach about sex education to students. The aim of this study was to determine students' understanding of sex education in forming the character of health care. This research is a qualitative conducted in SMA 1 Kualuh selatan using 2 techniques in data collection, namely in-depth interviews and questionnaires. The results of this study indicate that the average percentage of students' basic knowledge about sex education is sufficient (65.88%). This is due to a lack of levels of student concern for reproductive health and a lack of school roles, especially the role of Biology teachers.Keywords : Sex Education, Health Care, Biology Learning